Editorial (Journal of Health Informatics in Africa, 2021)
The Journal of Health Informatics in Africa is the official journal of the Pan African Health Informatics Association (HELINA) and publishes the proceedings of the HELINA conferences, as well as open-call issues. This issue is the second open-call issue for 2020 comprising of five research papers submitted directly to the journal. These papers  have  been  double  blind  peer-reviewed  before  being  accepted  for  publication.  Although  papers written in French are also published by the journal, all five papers in this issue was written in English. In addition to the five research papers, this issue also includes a Letter to the Editor that the JHIA Editorial Board considered very relevant and important to publish. The open letter was submitted by Neumann, Dunbar, Espino, Mtonga, and Douglas and highlights six themes that the authors consider important when developing Electronic Medical Records (EMRs) in low- and middle-income countries (LMIC). The authors believe that the consideration of these themes may support more careful exploration of creative, innovative, and sustainable EMR solutions that could ultimately improve patient outcomes through a positive impact on care delivery processes. The paper by Doualla, Bediang, Nganou-Gnindjio, Boombhi, and Kingue  presents the use of an electronic stethoscope coupled with tele-transmission and remote interpretation by a distant physician as a proof of concept of a tele-auscultation system in the assessment of cardiovascular diseases in remote areas of developing countries. Msendema investigates the question of how research, policy and practice in health information systems interface to guide design and implementation of health information systems. Authors Asah, Kanjo, Addo, Logo, Msendema explored the usability factors that influence the use of mobile technologies among healthcare staff at the point-of-care. Bbosa, Wesonga, Nabende, and Nabukenya reports on a hybrid data mining technique for predicting reliable malaria incidence rate thresholds that they developed. In their paper authors Olwendo, Otieno, and Rucha employed a retrospective cross-sectional study design in order to investigate the prevalence and complications associated with Diabetes Mellitus at the Nairobi Hospital in Kenya.    As we continue to live through the COVID 19 pandemic and its impact on both our work- and private lives, I realise the tremendous effort that went into completing this issue. The admirable commitment shown by authors that still managed to carefully prepare and submit manuscripts to JHIA, as well as the dedication of reliable peer-reviewers that took time out of their already busy schedules to assist with the review process. The editorial team also persevered under very difficult circumstances to manage the review and publication process and showed commendable determination to get this issue published. I would thus like to take the time to thank the editorial team, authors and peer reviewers that made this issue of JHIA possible. Your dedication, commitment, and perseverance is very much noted and appreciated.